Muza Enterprise - Karim, Faizal; Ariffin, Ariff Ilham; Kamaluddin, Muhammad Amirul Adli; Saum, Muhammad Ariff; Jasmi, Muhammad (2014)
MUZA ENTERPRISE is a business located in One Segamat, Segamat, Johor, that focuses on providing the nutritional benefits of bananas to both students and local residents. The enterprise serves walk-in customers and is committed to operating efficiently to ensure customer satisfaction. In addition to its main offerings, MUZA ENTERPRISE also sells two sizes of essence drinks bottles: small and large.